consider this equation

1/3 (6x - 9) = -33

Step 1:

Step 2:

Step 3:

1 answer

To solve the equation \( \frac{1}{3} (6x - 9) = -33 \), we can follow the steps below:

Step 1: Eliminate the fraction.
Multiply both sides of the equation by 3 to get rid of the fraction:

\[ 3 \cdot \frac{1}{3} (6x - 9) = 3 \cdot -33 \]

This simplifies to:

\[ 6x - 9 = -99 \]


Step 2: Isolate the term with \( x \).
Add 9 to both sides of the equation to move the constant term:

\[ 6x - 9 + 9 = -99 + 9 \]

This simplifies to:

\[ 6x = -90 \]


Step 3: Solve for \( x \).
Divide both sides of the equation by 6 to isolate \( x \):

\[ x = \frac{-90}{6} \]

This simplifies to:

\[ x = -15 \]

Thus, the solution to the equation \( \frac{1}{3} (6x - 9) = -33 \) is \( x = -15 \).

Similar Questions
    1. answers icon 1 answer
  1. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 43 answers
  2. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
  3. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
more similar questions